Enhancing rice yield and grain zinc concentration through strategic zinc application (Plant Bulletin, 2025)
Rice is a staple food globally, yet its grain zinc concentration is inherently low, contributing to widespread zinc deficiency. This study evaluated the effects of zinc application methods control, seed coating (2 g Zn kg⁻¹ seed), soil application (10 kg Zn ha⁻¹) and foliar spray (0.5% ZnSO₄) under two rice production systems: direct-seeded and transplanted. The experiment was conducted at the University of Agriculture, Faisalabad, during summer 2023 in a randomized complete block design with three replications. Foliar zinc application in transplanted rice produced the tallest plants (97.04 cm), highest productive tillers (367.67 m⁻²), longest panicles (27.18 cm) and maximum grain yield (4.75 t ha⁻¹). Grain zinc concentration increased from 14.87 mg kg⁻¹ in control to 30.24 mg kg⁻¹ under foliar zinc, showing a 103% rise. Overall, foliar zinc application was most effective for enhancing both yield and nutritional quality of rice.
Keywords: Rice, zinc application, foliar spray, seed coating, soil application and grain zinc